Codes and ciphers. - Gilbert, Adrian (London : QED, 2008)
"Discusses the difference between codes and ciphers, common codes and ciphers that have been used during wars, and how to create simple ciphers"--Provided by publisher.
Contents: Codes and ciphers -- The Caesar cipher -- Code breaking -- Morse code -- Visual codes -- Navajo code talkers -- One-time pads -- Cipher machines -- Purple intelligence -- Enigma -- Secret writing -- Microdots -- Radio communications. Notes: Includes index.
Keywords: Ciphers --Juvenile literature; Cryptography --Juvenile literature